2021
DOI: 10.18502/ijpa.v16i2.6311
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Frequency of Cystic Echinococcosis among Suspected Cases Referred to Health Centers Southwest Iran, and Post-Treatment Serologic Follow-Up

Abstract: Background: This study was designed to determine the frequency of hydatidosis in Khuzestan Province, Iran and to evaluate the antibody changes in infected individuals after treatment Methods: Overall, 454 sera were collected from health centers of Khuzestan Province, southern Iran (from 2013 to 2018). Demographic data such as age, gender and history of disease were recorded. Serum samples were investigated for antibody against CE by ELISA using antigen B. Thirty six of cases were followed up after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…In addition, Andrabi et al (19) reported that 6.31% of men versus 2.54% of women had IgG antibodies against E. granulosus. On the contrary, Rafiei et al (20) stated that seroprevalence in women was greater than in men (37.5% in males versus 62.5% in females). However, according to studies in Khuzestan, East Azerbaijan, and Sistan and Baluchistan provinces of Iran, the number of hydatid cysts surgical operations was higher in male than in female cases (21)(22)(23).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Andrabi et al (19) reported that 6.31% of men versus 2.54% of women had IgG antibodies against E. granulosus. On the contrary, Rafiei et al (20) stated that seroprevalence in women was greater than in men (37.5% in males versus 62.5% in females). However, according to studies in Khuzestan, East Azerbaijan, and Sistan and Baluchistan provinces of Iran, the number of hydatid cysts surgical operations was higher in male than in female cases (21)(22)(23).…”
Section: Discussionmentioning
confidence: 94%